Incidence, predictors and prognostic implications of positive circumferential resection margin in colon cancer: A retrospective study in a Chinese high-volume cancer center - Luo, Dakui; Li, Jing; He, Weijing; Yang, Yufei; Cai, Sanjun; Li, Qingguo; Li, Xinxiang (Frontiers in Oncology, 2022)
Positive circumferential resection margin (CRM) was associated with a higher recurrence rate and worse survival in rectal cancer. Predictors of CRM in rectal cancer have widely been investigated. Our study aims to determine the incidence, predictors and prognostic implications of positive CRM following colon cancer (CC) surgery in a Chinese high-volume cancer center. The clinicopathological features and oncological outcomes of CC patients undergoing surgery between January 2008 and December 2018 were identified from Fudan University Shanghai Cancer Center database. Positive CRM was defined as resection margin ≤1 mm. A total of 5268 stage I-IV CC patients were identified in our study, 108 (2.05%) of whom had positive CRM. Multivariate logistic analysis found that advanced N stage, distant metastases and poorly differentiated tumor had increased risk of positive CRM. After propensity score matching, the 5-year overall survival rates of the patients with positive and negative CRM were 33.2% and 39.8% (P=0.005), respectively. Multivariable COX regression model showed that positive CRM was an independent prognostic factor for OS in CC patients. The overall rate of positive CRM in our center is lower than that in western population. Several adverse pathological parameters deserve more attention to identify CC patients at a high risk of positive CRM. Adoption of appropriate surgical techniques and multidisciplinary treatment planning are expected to improve oncological outcomes for high selected CC patients with “high-risk” CRM involvement.